In vitro study of processing of the intron-encoded U16 small nucleolar RNA in Xenopus laevis. - Caffarelli, E (1994)
It was recently shown that a new class of small nuclear RNAs is encoded in introns of protein-coding genes and that they originate by processing of the pre-mRNA in which they are contained. Little is known about the mechanism and the factors involved in this new type of processing. The L1 ribosomal protein gene of Xenopus laevis is a well-suited system for studying this phenomenon: several different introns encode for two small nucleolar RNAs (snoRNAs; U16 and U18). In this paper, we analyzed the in vitro processing of these snoRNAs and showed that both are released from the pre-mRNA by a common mechanism: endonucleolytic cleavages convert the pre-mRNA into a precursor snoRNA with 5' and 3' trailer sequences. Subsequently, trimming converts the pre-snoRNAs into mature molecules. Oocyte and HeLa nuclear extracts are able to process X. laevis and human substrates in a similar manner, indicating that the processing of this class of snoRNAs relies on a common and evolutionarily conserved mechanism. In addition, we found that the cleavage activity is strongly enhanced in the presence of Mn2+ ions.